Late Holocene Historical Ecology: The Timing of Vertebrate Extirpation on Crooked Island, Commonwealth of The Bahamas. (2nd October 2017) - Steadman, David W.; Singleton, Hayley M.; Delancy, Kelly M.; Albury, Nancy A.; Soto-Centeno, J. Angel; Gough, Harlan; Duncan, Neil; Franklin, Janet; Keegan, William F.
ABSTRACT: We report eight new accelerator-mass spectrometer (AMS) radiocarbon ( 14 C) dates performed directly on individual bones of extirpated species from Crooked Island, The Bahamas. Three dates from the hutia ( Geocapromys ingrahami ), recovered from a culturally derived bone assemblage in McKay's Bluff Cave (site CR-5), all broadly overlap from AD 1450 to 1620, which encompasses the time of first European contact with the Lucayan on Crooked Island (AD 1492). Marine fish and hutia dominate the bone assemblage at McKay's Bluff Cave, shedding light on vertebrate consumption by the Lucayans just before their demise. A fourth AMS 14 C date on a hutia bone, from a non-cultural surface context in Crossbed Cave (site CR-25), is similar (AD 1465 to 1645) to those from McKay's Bluff Cave. From Pittstown Landing (site CR-14), an open coastal archaeological site, a femur of the Cuban crocodile ( Crocodylus rhombifer ) yielded an AMS 14 C date of AD ∼1050–1250, which is early in the Lucayan cultural sequence. From a humerus in a non-cultural surface context in 1702 Cave (site CR-26), we document survival of the Cuban crocodile on Crooked Island until AD ∼1300–1400, which is several hundred years later than the well-documented extinction of Cuban crocodiles on Abaco in the northern Bahamas. We lack a clear explanation of why Cuban crocodiles likely survived longer on Crooked Island than on a larger Bahamian island such as Abaco. One AMS 14 C date on Crooked Island's extinct, undescribed species of tortoise ( Chelonoidis sp.) from 1702 Cave is BC 790 to 540 (2740 to 2490 cal BP), which is ∼1500–1700 years prior to human arrival. A second AMS 14 C date, on a fibula of this tortoise from McKay's Bluff Cave, is AD 1025 to 1165, thereby demonstrating survival of this extinct species into the period of human occupation.